PENGARUH RESPONSIVITAS STREAMER DAN INTERAKSI LIVE STREAMING TERHADAP PARTISIPASI DONASI AUDIENS MAHASISWA PADA TIKTOK LIVE GAMING - Samantha Rebecca S. Silalahi; Nuriyatul Lailiyah (Interaksi Online, 2026)
The growth of gaming live streaming on TikTok has encouraged digital donation practices through Saweria as a form of audience participation. This study analyzes the influence of streamer responsiveness and live streaming interaction on audience participation in Saweria donations among student audiences watching TikTok Live Gaming, using a quantitative explanatory approach through a survey of 106 active Diponegoro University students, analyzed with multiple linear regression. The results show that streamer responsiveness and live streaming interaction have a positive and significant effect on donation participation, both partially and simultaneously (Sig. = 0.000), with streamer responsiveness as the more dominant predictor (Beta = 0.594) compared to live streaming interaction (Beta = 0.367), and a coefficient of determination (R²) of 0.902, indicating that higher streamer responsiveness and stronger interaction are associated with greater audience intention to donate via Saweria.